Life’s Hidden Resources for Learning: Conversations with a Radical Idea - Henshaw, Phil (Cosmos and History: The Journal of Natural and Social Philosophy, 2008)
One of the great mysteries of life is that science canrsquo;t find anything mysterious about it. This exploration approaches the question of lsquo;what is lifersquo; from looking at the blinders that science and other kinds of formal representational thinking have built into them which serve to hide the life.nbsp; Science teaches us to lsquo;make sensersquo; of things, using self-consistent models with no independent parts. We could use the same models to see the life in what departs from the models, pointing directly to the life of independent whole communities and organisms from which the emergent eventfulness of life seems to come. We donrsquo;t though. Not seeing the independent parts except as definitions gives us confusing lsquo;functional fixationsrsquo; and large mistakes. Any exploration begins with some accumulation of small steps, after stumbling around a bit to find a productive direction. Hopefully this will offer some productive stumbling around, and some places from which to begin an accumulation of small steps toward a whole new way of thinking about life. Scientific methods for exploring a living world are mentioned.